Endemic Plants on Karimunjawa Island as an Environmental Conservation Effort - Malik, Abdul (Al-Hayat: Journal of Biology and Applied Biology, 2022)
The study of endemic plants in the Karimunjawa Island area is an important concern in plant conservation efforts in protecting the surrounding environment. Endemic plants are unique and native plants that are found in an area and do not exist in other areas because of their small population. The research method used is Systematic Literature Review (SLR). SLR is a research method whose aim is to conduct ongoing and regularly updated systematic reviews, incorporating new, relevant evidence as it becomes available. The result there are three types of typical plants found in the Karimunjawa Islands, namely Dewadaru (Fragraea elliptica), Kalimasada (Cordia subcordata) and Setigi (Pemphis acidula). Dewadaru belongs to the Potalieae tribe. Potalieae is a homogeneous taxon that includes in general Fagraea, Anthocleista and Potalia. Water extract from Dewadaru fruit has been proven to be effective as a natural preservative for tofu, which contains alkaloids, flavonoids, phenolics, saponins and steroids barbarslot. Kalimasada (Cordia subcordata) belongs to the family (Boraginaceae) in the form of wood that is strong and durable, so it is good for use as building materials and household appliances. Cordia subcordata contains alkaloids, flavonoids, carbohydrates, glycosides, tannins, terpenoids. While Setigi (Pemphis acidula) is used as an ornamental plant (bonsai) with high economic value. Pemphis acidula can be used as a bioindicator of a mangrove area that is still beautiful because it is classified as a pure standing mangrove type. The ethanol extract of pandemor leaf simplicia (Pemphis acidula) contains a class of flavonoids, saponins and tannins.